State formation in early modern Alsace, 1648-1789 - Lazer, Stephen A., 1983- (Changing perspectives on early modern Europe., 2019)
"A documented study of early modern state formation, sovereignty, legitimacy, and comparative political culture in Alsace between the Peace of Westphalia and the French Revolution"--